E-cigarette and marijuana use and the attainment of obesity prevention guidelines among U.S. adolescents - Wura Jacobs; Laura Nabors; Melinda E. Mahabee-Gittens; Ashley L. Merianos (Preventive Medicine Reports, 2021)
The study objectives were to examine the associations of exclusive and dual use of e-cigarettes and marijuana and the attainment of the “Let’s Go! 5–2-1–0” obesity prevention guidelines and perceptions of weight status among U.S. adolescents. Data from the 2017 Youth Risk Behavior Survey, a school-based nationally representative cross-sectional study, were analyzed (N = 12,578). Participants were categorized based on their past 30-day e-cigarette and marijuana use as: non-users, exclusive e-cigarette users, exclusive marijuana users, and dual users. Adjusted logistic regression models were conducted. Of adolescents, 5.2% were exclusive e-cigarette users, 10.3% were exclusive marijuana users, and 7.4% were dual users. Compared to non-users, exclusive e-cigarette users were more likely (aOR = 1.55, 95%CI = 1.16–2.07) to meet the physical activity recommendation. Compared to dual-users, exclusive e-cigarette users were more likely (aOR = 1.47, 95%CI = 1.10–1.97) to meet the screen time recommendation. Compared to non-users, exclusive marijuana users were at increased odds to meet the fruit/vegetable recommendation (aOR = 1.33, 95%CI = 1.03–1.71), but were at decreased odds to meet the sugar-sweetened beverages recommendation (aOR = 0.81, 95%CI = 0.65–0.99). Compared to exclusive e-cigarette users, exclusive marijuana users were less likely to meet the screen time (aOR = 0.71, 95%CI = 0.54–0.93) and physical activity recommendations (aOR = 0.60, 95%CI = 0.43–0.84). Compared with dual users, exclusive marijuana users were more likely (aOR = 1.38, 95%CI = 1.01–1.88) to perceive themselves as slightly/very overweight. Compared to non-users, dual users were less likely to meet the sugar-sweetened beverages recommendation (aOR = 0.63, 95%CI = 0.46–0.87). Adolescent current marijuana users and dual users were less likely to meet obesity prevention guidelines. Prevention efforts are needed to reduce e-cigarette and marijuana use and increase adherence to these guidelines.